Occupation and metabolic syndrome: is there correlation? A cross sectional study in different work activity occupations of German firefighters and office workers. Issue 1 (December 2016) - Strauß, Markus; Foshag, Peter; Przybylek, Bianca; Horlitz, Marc; Lucia, Alejandro; Sanchis-Gomar, Fabian; Leischik, Roman
Abstract Background The treatment and prevention of the metabolic syndrome (MetS) is currently one of the major challenges in medicine. The impact of working conditions on metabolic risk has not been adequately studied. Our objective was to compare the prevalence of MetS and metabolic risk in two extremely different occupational groups: firefighters and office workers. Methods A total of 143 male subjects (97 firefighters and 46 office workers) from Germany participated in the study. Anthropometric characteristics, metabolic risk parameters as well as laboratory parameters were collected. MetS was diagnosed according to criteria of the International Diabetes Federation. Results Sedentary occupation showed a significant tendency towards obesity. Abdominal waist circumference was significantly greater in office workers than in firefighters [5.08 CI (1.44–8.71), p = 0.007]. Concerning metabolic risk factors, abnormal HDL, triglycerides, BMI, blood pressure and waist circumference values were more frequently found in office workers than in firefighters. The MetS was detected in almost 33 % of office workers as compared with only 14 % in firefighters (p = 0.015). Regarding MetS in an international comparison, the prevalence of MetS in German office workers was high and in firefighters it was extremely low. Conclusions Sedentary occupation as an office worker is associated with a high risk of MetS. Both groups need to be made aware of the metabolic risks, and health promoting concepts such as corporate sports activities or education in healthy nutrition need to be implemented to counteract the development of the MetS and cardiovascular risk factors.